Педагогічні умови формування професійної компетентності фахівців-музикантів з арт-менеджменту - Татарнікова, Анжелика Анатоліївна; Татарнікова, А. А.; Tatarnikova, Anzhelyka A. (My University, 2016)
У статті на основі аналізу та узагальнення концептуальних підходів зарубіжних та українських учених щодо сутності навчальних програм з арт-менеджменту, а також модернізації мистецької освіти обгрунтовано педагогічні умови формування професійної компетентності студентів музичних спеціальностей з арт-менеджменту. Продемонстровано значущість професійної підготовки студентів музичних спеціальностей як майбутніх арт-менеджерів, розкрито дидактичну потужність провідних принципів та засобів компетентнісного й студентоцентрованого підходів щодо її організації та оцінки якості прикінцевих результатів. The article deals with the justification of the pedagogical conditions for the development of professional competence of music students specialized in arts management, which is based on the analysis of the conceptual approaches of foreign and Ukrainian scientists to studying the content of educational programmes on arts management, as well as the modernisation of professional music education system. The importance of training music students-future arts managers is also demonstrated in the article. The future specialists should master advanced technologies of arts management, i.e. art products promotion, concert administration, information support of art products and performer’s creative work, Internet promotional campaigns, blogging in social networks, collaboration with sponsors (fundraising, patronage, and charity), etc. The analysis of educational curricula and programmes, as well as the empirical study on the levels of professional competence of music graduates specialized in arts management in Ukraine conclusively confirm the fact that personality of a graduate as a professionally competent arts manager in the field of musical art has not been developed intentionally and in a proper way until now. Therefore, the didactical potential of the main principles and means of competency-based and student-oriented approaches to its organisation and the results evaluation is elicited. It is also proved that the development of professional competence of music students specialized in arts management in the course of receiving their degree will be more efficient in case certain pedagogical conditions are created in the education process: providing the content of artistic education with the theoretical issues of arts management, supporting students’ individual research activities on mastering advanced technologies of arts management, the pedagogical support of individual and professional self-development of students as arts managers in the field of musical art, and motivating students to participation in different project artistic and creative activities. It is shown that the means of the student- oriented approach, particularly, the principles of humanization; individualization; personalization; dialogization; scientificity; occupational mobility; contextuality of education; diversification of artistic education, its universality; relevance of its content, forms and methods to contemporary targets and functions of a professional musician as an arts manager; the combination of pedagogical facilitation and the development of initiatives and leadership of the members of the social and cultural environment; the problemacity and situatedness of education, its close relation to the arts management practice contribute to the practical implementation of the indicated pedagogical conditions.
Татарнікова А. А. Педагогічні умови формування професійної компетентності фахівців-музикантів з арт-менеджменту / А. А.Татарнікова // "Наука і освіта". - 2016. - №4. - С. 5-10. Режим доступу: https://hdl.handle.net/11300/28391
Keywords: арт-менеджмент; професійна компетентність з арт-менеджменту; компетентністний підхід; студентоцентрований підхід; фахова підготовка студентів музичних спеціальностей